Phallus dongsun and P. lutescens, two new species of Phallaceae (Basidiomycota) from China - Li, Ting; Li, Taihui; Deng, Wangqiu; Song, Bin; Deng, Chunying; Yang, Zhu L. (Phytotaxa, 2020)
“Dongsun” is an edible species of Phallus commercially cultivated in China. It is morphologically similar to P. impudicus and actually has been misidentified as “P. impudicus” for a long time. In this study the Chinese “Dongsun” is confirmed to be different from the typical P. impudicus from Europe based on morphological and phylogenetic comparisons, and therefore is formally proposed as P. dongsun, a species new to science. At the same time, another new species of Phallus was also discovered from southern China. It is named as P. lutescens, and is morphologically characterized by its indusium colour that turns from white or cream white to yellow or yellow-orange when mature. Both new species are presented with detailed morphological descriptions, photographs of basidiomata and images of microscopic structures, and are compared with other related Phallus taxa based on morphological and molecular data. A key to the Phallus species without an indusium and a key to the Phallus species with a coloured indusium are also presented at the end of the text.